2017
DOI: 10.1152/jn.01009.2015
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of muscle activity in rapid responses to startling cues

Abstract: We demonstrate that the ability to activate muscles selectively is preserved during the very rapid reactions produced following a startling cue. This suggests that the contributions from different descending pathways are comparable between these rapid reactions and more typical voluntary movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
5
26
1
Order By: Relevance
“…Indeed, the patterns of cortical movement-related activity in the quasi-automatic context were 616 very similar to those in the other two contexts. As in 45 , we do not suggest an absence of sub-cortical 617 involvement, merely a conservation of cortical involvement. 618…”
Section: Cortical Involvement Despite Fast Rts 599contrasting
confidence: 74%
See 1 more Smart Citation
“…Indeed, the patterns of cortical movement-related activity in the quasi-automatic context were 616 very similar to those in the other two contexts. As in 45 , we do not suggest an absence of sub-cortical 617 involvement, merely a conservation of cortical involvement. 618…”
Section: Cortical Involvement Despite Fast Rts 599contrasting
confidence: 74%
“…Yet a recent study argued against a reduction of cortical involvement in StartReact 45 . The authors instead 607…”
Section: Cortical Involvement Despite Fast Rts 599mentioning
confidence: 99%
“…Therefore, separating trials by their latencies is likely to be more indicative of a mechanism that bypasses or activates specific mechanisms in the central nervous system than relying on surface EMG (see also [37]. To decide which percentiles would be representative of values obtained when using SCM to separate trials (SCM+ and SCM-), we fitted a CDF to data kindly provided by Honeycutt As shown in Figure 6A, this main effect was qualified by a significant interaction between IS predictability and IS timing (F (2,253) = 18.66, p < .0001, LR = 24.36), suggesting the effect of IS timing was stronger in the unpredictable block of trials.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative view to this triggering through subcortical areas, the shortening of RT seen in the StartReact effect may be a product of an enhancement of voluntary motor pathways via an engagement of a more widespread cortical-subcortical network when an intense sensory stimulus is presented (see Marinovic & Tresilian, 2016). The difficulties in determining neurophysiological mechanisms underlying the early triggering of motor responses using the presence or absence of SCM activity has been outlined previously (Dean & Baker, 2017;Leow et al, 2018;Marinovic & Tresilian, 2016;McInnes, Corti, Tresilian, Lipp, & Marinovic, 2020) and it seems SCM activity can be an unreliable indicator of distinct mechanisms that can be activated by intense sensory stimuli. Rather, determination of the presence of a specific StartReact mechanism may be more feasible when trials are separated based on their response latency (Leow et al, 2018;McInnes et al, 2020).…”
Section: Introductionmentioning
confidence: 98%